Susan’s Elusive Unreliability and Coetzee’s Existential Thinking in Foe - Yinqi Zhao (Randwick International of Social Science Journal, 2023)
This paper explores the portrayal of Susan Barton as an unreliable narrator in J.M. Coetzee’s novel, Foe, and its implications on storytelling, authorial authority, and existential themes. Through a comprehensive analysis of Susan’s narrative, the paper delves into the dual interpretations of her (un)reliability and argues that Coetzee intentionally crafts her as an elusive unreliable narrator. Then this article examines the “re-deconstruction” achieved by Coetzee, which challenges traditional storytelling conventions and emphasises the underlying meaning conveyed by a story. It also tries to explore Coetzee’s philosophical contemplations of existence and contends that aligning with Sartre’s existential thinking, Coetzee discusses many concepts around freedom and existence. By incorporating existential reflections, the paper uncovers the consciousness and existence embedded in the narrative.